Factors involved in the clinical profile of carpal tunnel syndrome - Puchalski, Piotr; Zyluk, Paulina; Szlosser, Zbigniew; Zyluk, Andrzej (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
Clinical presentation of carpal tunnel syndrome may differ in relation to certain factors like sex, age, duration of symptoms and severity of compression. The objective of this study was an investigation into the hypothesis that several distinct factors are predictive of the clinical profile for the condition. The records of 1,117 patients: 909 women (81 %) and 208 men (19 %) with a mean age of 63 years, were analysed. The whole group was divided into subgroups, depending on the variables analysed: sex, age, duration of the condition, severity of symptoms, severity of electrophysiological abnormalities and occurrence or lack of comorbidities. Results. Of all the considered variables, the Levine symptom scores had the greatest impact on the condition’s clinical profile: the higher scores the more severe pain, poorer sensation, weaker grip and worse hand function. Also, ages greater than 80 years had a significant negative effect on most of the considered parameters. None of the remaining analysed variables had a substantial impact on the clinical profile of the condition.
Keywords: carpal tunnel syndrome; clinical presentation